The Effect of Mix Impact Aerobic Exercise on Cardiovascular Improvement at Penggemar Senam Pagi Sungai Kambang Ceria (PSPSKC) Community - Sukendro; Yeni Kurniawati; Yusra Dinafi; Turino Adi Irawan; Yonifia Anjanika; Putri Ayu Lestari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
The circulatory system or cardiovascular system is an organ system that functions to move substances to and from cells. The term cardiovascular ability has the same meaning as several other terms such as cardiac endurance, aerobic fitness, and cardiorespiratory endurance. In the Penggemar Senam Pagi Sungai Kambang Ceria (PSPSKC) community, there is a lack of physical activity, a lack of application of the right time to do sports and less precise in choosing sports exercises that can improve cardiovascular. Because the members need to have good cardiovascular endurance to support daily activities.This type of research is an experimental research with a one group pre-test post-test design. The instrument used is the Harvard step test. The population in this study were the entire Senam Pagi Sungai Kambang Ceria (PSPSKC) community which amounted to 64 people. Sampling in this study using purposive sampling technique, namely the technique of determining the sample with a specific purpose. The sample in this study were 10 people from the Penggemar Senam Pagi Sungai Kambang Ceria (PSPSKC) community aged 20-30 years. The results of the research on the initial test (pre-test) got an average result of 57.3 while in the final test (post-test) it was 65.3. Meanwhile, from the results of hypothesis testing using the t-test, the results of t (4.457)> from the t value (1.833) with a significance level of = 0.05 (5%). From these data, it can be concluded that there is a significant effect of Mix Impact aerobic exercise on cardiovascular improvement in the Penggemar Senam Pagi Sungai Kambang Ceria (PSPSKC) community.